The Expanding Toolbox of In Vivo Bioluminescent Imaging - Xu, Tingting; Close, Dan; Handagama, Winode; Marr, Enolia; Sayler, Gary; Ripp, Steven (Frontiers in Oncology, 2016)
In vivo bioluminescent imaging (BLI) permits the visualization of engineered bioluminescence from living cells and tissues to provide a unique perspective toward the understanding of biological processes as they occur within the framework of an authentic in vivo environment. The toolbox of in vivo BLI includes an inventory of luciferase compounds capable of generating bioluminescent light signals along with sophisticated and powerful instrumentation designed to detect and quantify these light signals non-invasively as they emit from the living subject. The information acquired reveals the dynamics of a wide range of biological functions that play key roles in the physiological and pathological control of disease and its therapeutic management. This mini review provides an overview of the tools and applications central to the evolution of in vivo BLI as a core technology in the preclinical imaging disciplines.